2017
DOI: 10.1155/2017/4373859
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Power Ultrasound on Antihypertensive Activity, Functional Properties, and Thermal Stability of Rapeseed Protein Hydrolysates

Abstract: The effects of power ultrasound pretreatments on the degree of hydrolysis (DH), angiotensin-I-converting enzyme (ACE) inhibitory activity, amino acid composition, surface hydrophobicity, protein solubility, and thermal stability of ACE inhibition of rapeseed protein hydrolysates were evaluated. Ultrasonic pretreatments before enzymolysis in terms of power and exposure time increased the DH and ACE inhibitory activities over the control (without sonication). In this study, maximum DH 22.07% and ACE inhibitory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 67 publications
3
18
0
Order By: Relevance
“…However, the angiotensin‐converting enzyme inhibitory activity mediated by the rapeseed and casein‐derived protein hydrolysate/peptides significantly decreased when heated at temperatures above 100 °C. However, it should be noted that the duration of thermal treatment was 1 and 2 h, respectively (Wu et al ., 2014; Wali et al ., 2017). Antioxidant peptides derived from Jinhua ham were shown to be less thermostable than the protein hydrolysate/peptides described above (Zhu et al ., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the angiotensin‐converting enzyme inhibitory activity mediated by the rapeseed and casein‐derived protein hydrolysate/peptides significantly decreased when heated at temperatures above 100 °C. However, it should be noted that the duration of thermal treatment was 1 and 2 h, respectively (Wu et al ., 2014; Wali et al ., 2017). Antioxidant peptides derived from Jinhua ham were shown to be less thermostable than the protein hydrolysate/peptides described above (Zhu et al ., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The results reported herein are consistent with the findings of Lai et al (2016), who showed that walnut protein hydrolysates were stable and retained their antioxidant activity following heat treatment at 65°C 9 30 min and 121°C 9 20 min. Furthermore, the bioactivity exhibited by rapeseed, tuna cooking juice and bovine casein-derived protein hydrolysate/ peptides was reported to be stable when subjected to temperatures in the range 0-100°C (Hwang, 2010;Wu et al, 2014;Wali et al, 2017). However, the angiotensin-converting enzyme inhibitory activity mediated by the rapeseed and casein-derived protein hydrolysate/ peptides significantly decreased when heated at temperatures above 100°C.…”
Section: Selection Of Hydrolysate Delivery Vehicle and Assessment Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, more potent ACE inhibitory [94] and antioxidant [95] peptides were released after applying an ultrasound step before hydrolysis of wheat protein. More recently, the improvement of the ACE inhibitory activity of rapeseed protein hydrolyzates has been demonstrated [96]. Ultrasound has also been employed to increase the bioactivities of hydrolyzates from animal proteins such as milk and whey protein [88,97] and ovotransferrin [98].…”
Section: Release Of Bioactive Peptidesmentioning
confidence: 99%
“…Lately, scientists have been testing enzymatic hydrolysis carried out after or during the application of non-thermal techniques, such as high pressure, ultrasound or microwave. The global conclusions are that high hydrostatic pressure and ultrasound pre-treatment improve the efficacy of enzymatic hydrolysis and the consequent release of bioactive peptides [60][61][62][63]. Regarding the protein structure, the tertiary and quaternary structures are generally affected by high-pressure treatment, while the secondary structures tend to be maintained.…”
Section: Enzymatic Hydrolysis Reactionmentioning
confidence: 99%